Evaluation of daytime sleepiness and insomnia symptoms in OSA patients with a characterization of symptom-defined phenotypes and their involvement in depression comorbidity—a cross-sectional clinical study - Gabryelska, Agata; Turkiewicz, Szymon; Białasiewicz, Piotr; Grzybowski, Filip; Strzelecki, Dominik; Sochal, Marcin (Frontiers in Psychiatry, 2024)
Introduction. Recent research highlights the significance of insomnia and sleepiness, shifting from OSA severity and sleep structure, in defining OSA phenotypes. Objectives. The study aimed to characterize insomnia and sleepiness associated with OSA phenotypes and assess their involvement in depression symptoms (DS) in OSA. Materials and methods. This cross-sectional, clinical study included 181 participants who underwent polysomnography (PSG) and filled out questionnaires, including the Epworth Sleepiness Scale (ESS), Insomnia Severity Index (ISI), Pittsburgh Sleep Quality Index (PSQI), and Beck Depression Index (BDI). They were categorized into phenotypes: insomnia-sleepiness (I+S; ESS≥11; ISI≥15; n=20), sleepiness (S; ESS≥11; ISI<15; n=22), insomnia (I; ESS<11; ISI≥15) and asymptomatic (A; ESS<11; ISI<15; n=55). Results. A linear regression model for the BDI score (R2=0.357, p<0.001) included ISI score and subjective to objective sleep latency ratio. ISI score was a predictive factor for mild and moderate DS (OR=1.23 (95%CI: 1.09-1.38), p<0.001 and OR=1.39 (95%CI: 1.13-1.72), p=0.002). I and I+S phenotypes are characterized by higher BDI scores (p<0.001 and p=0.02), longer subjective sleep latency (p=0.008 and p=0.04), and shorter subjective total sleep time (TST; p=0.049 and p=0.006), compared to A. Furthermore, the I and I+S groups had shorter subjective TST than S (p=0.03 and p=0.047). I and I+S had higher BDI scores than A (p<0.001 and p=0.02, respectively) and S (p<0.001 and p=0.02, respectively). I phenotype was associated with the risk of mild and moderate DS (OR=5.61 (95%CI: 1.91-16.53), p<0.001 and OR=9.55 (95%CI: 1.81-50.48), p=0.008 respectively). Moreover, the I+S phenotype presented an even greater risk for mild DS (OR=10.29 (95%CI: 2.95-35.85), p<0.001). Conclusion. Using clinical features for OSA phenotyping holds promise for finding OSA individuals with increased risk for DS occurrence.